Evaluation of effectiveness of intracanal medicaments on viability of stem cells of apical papilla - Gaurav Jain; Akriti Goel; Balakrishnan Rajkumar; Ravinder Singh Bedi; Divya Bharti; Anuradha Sawardeker (Wolters Kluwer Medknow Publications, 2020)
Introduction: Regeneration, in the field of endodontics, is the process of restoring and maintaining both architectural form and biological functions of damaged tooth. Presently, regenerative endodontics is not hypothetical and is an alternative to conventional apexification procedures. There is a deficient knowledge concerning the role of intracanal medicaments and their effect on dental stem cells. Aim: The aim of this study was to evaluate the effectiveness of commonly used intracanal medicaments on the viability of dental stem cells of the apical papilla (SCAPs). Materials and Methods: SCAPs were cultured and subjected to various concentrations including triple antibiotic paste, double antibiotic paste, Augmentin, and calcium hydroxide (Ca(OH)2). Viable percentage of stem cell counts was obtained 3 days after treatment. Results: All three antibiotics used hereby significantly decreased SCAP cell survival at particular concentrations, whereas Ca(OH)2 showed stimulating effect on SCAP survival. Conclusion: As per results obtained within limitations of this study, use of Ca(OH)2 in regenerative endodontics in comparison to different commonly used antimicrobial combinations is recommended. Hereby, for clinical use, we suggest adequate concentrations of antimicrobials with adequate antibacterial efficacy should be used.